(untitled) (Journal of Engineering, 2012)
Experimental work was carried out to investigate the effect of fire flame (high temperature) on specimens of one way slabs using Self Compacted Concrete (SCC). By using furnace manufactured for this purpose, twenty one reinforced concrete slab specimens were exposed to direct fire flame. All of specimens have the same dimensions. The slab specimens were cooled in two types, gradually by left them in the air and suddenly by using water. After that the specimens were tested under two point loads, to study, the effect of different: temperature levels (300ºC, 500ºC and 700ºC), and cooling rate (gradually and sudden cooling conditions) on the concrete compressive strength, modulus of rupture, flexural strength and the behavior of reinforced concrete slab specimens and comparing the results with specimens without burning (reference specimens). The results showed that, the concrete compressive strength, concrete modulus of rupture and the flexural strength decreases while the maximum (central) deflection increases with increasing the fire flame temperature. For suddenly cooled specimens the residual flexural strength is less than that of gradually cooled specimens while the deflection is greater. For slabs with 20 MPa concrete strength and gradually cooled, the residual bending strength percent is 81.5%, 75% and 62.3% ,while the increase in central deflection is 5%, 33%, and 105% at burning temperature 300ºC, 500ºC and 700ºC respectively. For suddenly cooled specimens of the same strength and exposed to the same temperatures above the residual flexural strength is 77.9%, 68.3% and 58.3% while the increase in central deflection is 25%, 52%, and 118% respectively. When the strength of concrete specimens increase, the residual flexural strength experiences small increase and the increase is of lower rate in the central deflection for 300 ºC and 500 ºC burn temperatures while the decrease is significant for 700 ºC burning temperature.